Memorias del Congreso Latinoamericano de Computación de Alto Rendimiento (CLCAR) - Query and data caching in grid middleware - D'Orazio, Laurent; Labbé, Cyril; Roncancio, Claudia (SABER ULA, 2008)
Query and data caching in grid middleware. (D’Orazio, Laurent; Labbé, Cyril y Roncancio, Claudia) Abstract Caching is crucial to improve performances in many computing systems. This work proposes a caching approach for improving query evaluation. The proposed solution follows a semantic oriented approach and combines query and object caching. Separating query and objects provides high flexibility, by making possible to use several cooperations between caches and by supplying different query management tools. Our proposition has been experimented in a grid data management middleware and seems promising as showed by the results reported in this paper. Ponencia publicada en: Memorias del Congreso Latinoamericano de Computación de Alto Rendimiento (CLCAR) Santa Marta, Colombia 13 al 18 de agosto 2007. J.C. Jaime y G. Díaz (editores), Publicaciones Univ. Industrial de Santander, Bucaramanga, Colombia (2007).
Keywords: Memorias; Computación; Facultad de Ingeniería; Facultad de Ciencias.; Artículos